TEACHING RESEARCH METHODOLOGY (TRM) AND SUPERVISING RESEARCH WORK (SRW): CONCEPTIONS, DIFFICULTIES, AND PRACTICES OF LEBANESE UNIVERSITY INSTRUCTORS - Shaaban, Eman; Yammine, Assaad; Khalil, Iman (International Journal of Research -GRANTHAALAYAH, 2021)
Research methodology is an essential subject in higher education, however, it is challenging to instructors because of the complexity of the course material. This study aims to highlight the conceptions, difficulties and practices of the Lebanese University research methodology instructors and research work supervisors. For this purpose, research experts constructed and validated a questionnaire. 81 instructors and / or supervisors voluntarily participated. Results showed diversification in conceptions of participants with respect to some common essential concepts within the framework of research methodology, this reflects the complexity of the content and can hinder teaching research methodology (TRM) as well as supervising research work (SRW). Moreover, the participants indicated that they face many difficulties during SRW. The majority of the instructors elaborate their own resources for teaching methodology, they implement student-centered teaching methods and variety of assessment methods allowing students to explore and practice methodology concepts. In addition, they update their knowledge and practices on their own by attending conferences, performing research, discussing with colleagues, and by reflecting on their practices. Thus, our findings imply the need to precise the competencies required for TRM and SRW, and to encourage instructors and supervisors to reflect on their practices and share their experiences.